Transhumanismo y el desarrollo de problemas bioéticos en la práctica médica - Barriga Avalos, Yajaira Brigitte (2025)
Transhumanism is a movement of a philosophical, scientific, and technological nature that seeks to enhance human capabilities through the use of techniques such as artificial intelligence (AI), nanotechnology, biotechnology, and cybernetics (NBCI). The aim is, in this way, to transcend the limits of the human being, although it generates bioethical and social dilemmas regarding identity, justice, and medical risks. Objective: To describe the literature referring to the bioethical dilemmas of transhumanism in medical practice in order to obtain responses that allow for the improvement of the quality of medical care provided; Methods: A descriptive study was conducted through a bibliographic review of scientific sources that show the ethical dilemmas that appear in medical practice that makes use of transhumanism; Results: There could be a case of disarticulation of the doctor-patient relationship, as the progressive use of technology in the diagnosis and treatment process would lead to a reduction in human interaction and to turning the patient into a condition to be managed, which also generates new demands on the improvement of the human being; Conclusions: Emphasis is placed on the progressive dehumanization of medical practice and the lack of regulatory means for the use of NBIC; emphasis is placed on the need to construct ethical norms that regulate the practice of medicine and the behaviors that accompany this practice; finally, the need to carefully assess how transhumanism and the accelerated development of technologies in medicine translate, as their implications are global, is highlighted.